2017
DOI: 10.3390/ijms19010005
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Gonadotropins, Prolactin and Growth Hormone Differentially Regulate AQP1 Expression in the Porcine Ovarian Follicular Cells

Abstract: The present in vitro study analyzed whether the hormones that affect the ovarian follicular steroidogenesis process also participate in the regulation of AQP1 mRNA and protein expression. Granulosa (Gc) and theca cells (Tc) of medium and large porcine ovarian follicles were exposed to follicle-stimulating hormone (FSH), luteinizing hormone (LH), prolactin (PRL) and growth hormone (GH) for 24 h in separated cells and co-cultures of these cells. Real-time PCR, Western blotting, immunofluorescence and volumetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…It was widely thought that granulosa cells (GCs) supported the development and maturation of follicles though the complex interactions [ 5 , 6 ], and that the growth and proliferation of GCs play critical roles in the biological processes of recruitment, selection, atresia, ovulation and luteolysis of follicles [ 7 , 8 ]. Previous studies have found that steroids, growth factors, and cytokine factors secreted by GCs are essential for the survival and growth of follicles [ 9 , 10 ], and moreover, the high apoptosis of GCs can impair folliculogenesis and result in the increased follicular atresia [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was widely thought that granulosa cells (GCs) supported the development and maturation of follicles though the complex interactions [ 5 , 6 ], and that the growth and proliferation of GCs play critical roles in the biological processes of recruitment, selection, atresia, ovulation and luteolysis of follicles [ 7 , 8 ]. Previous studies have found that steroids, growth factors, and cytokine factors secreted by GCs are essential for the survival and growth of follicles [ 9 , 10 ], and moreover, the high apoptosis of GCs can impair folliculogenesis and result in the increased follicular atresia [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In previous research [28] we found a stimulatory effect of FSH and LH on AQP1 mRNA and protein expression in the Gc ant Tc of pig medium and large ovarian follicles and co-cultures of these cells. In the present research, AQP5 was mainly submitted to the regulatory effect of FSH and LH, since these hormones markedly increased AQP5 mRNA and protein expression in Gc and Tc, as well as in co-cultures of the cells.…”
Section: Discussionmentioning
confidence: 76%
“…Inspiration for this study came from the earlier results obtained from the pig [28]. The study found that follicle-stimulating hormone (FSH), luteinizing hormone (LH), prolactin (PRL), and growth hormone (GH) regulated AQP1 expression in the ovarian follicular cells of pigs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations